Hyperbaric oxygen therapy for complications of breast cancer surgery - Batista Fernandes, Carolina; Vieira, Roberto; Barbosa, Marcelo; Valente, Emanuelle Narciso Alvarez; Adeodato Bello, Marcelo; Ricardo Chagas, Carlos; Roustand Rabay Kunz, Maria Helena; Pereira de Castro, Marcio Aurélio (Mastology, 2025)
In 2020, there were approximately 2.3 million new cases of breast cancer worldwide. Breast-conserving surgery followed by adjuvant radiotherapy has replaced radical and modified radical mastectomy as the standard treatment for patients with early-stage breast cancer, with equivalent overall survival and disease-free survival rates. Oncoplastic techniques consist in removing the tumor from the breast and applying plastic surgery techniques for breast reconstruction. The use of oncoplastic techniques may increase the number of women who experience postoperative complications or who are recalled for biopsy. Complication rates of around 16% can be considered acceptable, with the most common immediate complications being delayed wound healing, fat necrosis, and infection, while late complications being fibrosis and breast asymmetry. The use of hyperbaric oxygen therapy (HBOT) appears as an alternative for the treatment of these conditions. The Undersea and Hyperbaric Medical Society recognizes 14 valid medical indications for HBOT. Among these, those that stand out with interest in mastology are: chronic wounds; compromised flaps and grafts; radiotoxicity and soft tissue infections. Although most of the evidence is the result of observational studies or is extrapolated from the use of HBOT in other areas, its use may contribute to better outcomes in patients undergoing surgical treatment for breast cancer.